2001
DOI: 10.4049/jimmunol.166.11.6899
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor CCR4 on CD4+ T Cells in Juvenile Rheumatoid Arthritis Synovial Fluid Defines a Subset of Cells with Increased IL-4:IFN-γ mRNA Ratios

Abstract: To understand the mechanisms that promote recruitment and survival of T cells within the pediatric inflamed joint, we have studied the expression of CCR4 and CCR5 on synovial fluid T cells and matched peripheral blood samples from juvenile rheumatoid arthritis (JRA) patients using three-color flow cytometric analysis. Thymus- and activation-regulated chemokine and macrophage-derived chemokine, ligands for CCR4, were measured by ELISA in JRA synovial fluid, JRA plasma, adult rheumatoid arthritis synovial fluid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…Chemokines, which are induced by inflammatory cytokines in the inflamed joint tissue, facilitate the cellular influx to the joints during arthritis. T lymphocytes expressing the chemokine receptors CXCR3, CCR2, CCR4, CCR5, CXCR6, and others are present in RA joint tissue (1)(2)(3)(4)(5)(6). Similarly, levels of CXC and CC chemokine ligands, such as CXCL10, CXCL11, CCL2, CCL3, CCL5, and others are found in abundance in synovial fluids of patients with RA (4,5,7,8).…”
Section: R Heumatoid Arthritis (Ra)mentioning
confidence: 95%
“…Chemokines, which are induced by inflammatory cytokines in the inflamed joint tissue, facilitate the cellular influx to the joints during arthritis. T lymphocytes expressing the chemokine receptors CXCR3, CCR2, CCR4, CCR5, CXCR6, and others are present in RA joint tissue (1)(2)(3)(4)(5)(6). Similarly, levels of CXC and CC chemokine ligands, such as CXCL10, CXCL11, CCL2, CCL3, CCL5, and others are found in abundance in synovial fluids of patients with RA (4,5,7,8).…”
Section: R Heumatoid Arthritis (Ra)mentioning
confidence: 95%
“…In these children, the disease frequently involves a nonremitting destructive and disabling arthritis, requiring aggressive immunosuppressive therapy. It is still not known which mechanisms determine this wide difference in clinical appearance between the two subtypes, although evidence is accumulating that T cells, such as CCR4-expressing T cells and T cells specific for heat shock protein 60, play a key role (17)(18)(19).…”
Section: It Is Now Clear That Cd4mentioning
confidence: 99%
“…Various studies have indicated that CCR4 and its ligands may play a role in this pathological condition (4,(11)(12)(13)(14)(15)(16)(17). CCR4 and/or CCL17/CCL22 have also been implicated in atopic dermatitis (5,18,19), endotoxic shock (20), rheumatoid and juvenile rheumatoid arthritis (21,22), migration of leukemia-specific T cells (23), Fulminant hepatic failure (24), Hodgkin's lymphoma (25), and T cell non-Hodgkin lymphoma (26).…”
mentioning
confidence: 99%